Association between ABCB1 polymorphism and response to sodium valproate treatment in Malaysian epilepsy patients - Haerian, B.S.; Lim, K.S.; Tan, H.J.; Mohamed, E.H.M.; Tan, C.T.; Raymond, A.A.; Wong, C.P.; Wong, S.W.; Omar, H.; Roslan, H.; Mohamed, Z. (2011)
Over-expression of P-glycoprotein, encoded by the ABCB1 gene, is proposed to be involved in resistance to antiepileptic drugs in about 30 of patients with epilepsy. Here, we investigated the possible association between ABCB1 polymorphisms and sodium valproate (VPA) treatment in Malaysian epilepsy patients. Genotypeswere assessed in 249 drug-resistant and 256 drug-responsive Malaysian patients for C1236T, G2677T/A, and C 5T polymorphisms in the ABCB1 gene. No genotypes, alleles, or haplotypes were associated with the response to VPA in either the overall group or Chinese, Indian, and Malay subgroups. Our data suggest that C1236T, G2677T/A, and C3435T polymorphisms in the ABCB1 gene do not contribute to the response to VPA in patients with epilepsy.